Application of the Ugi reaction with multiple amino acid-derived components: synthesis and conformational evaluation of piperazine-based minimalist peptidomimetics1. Issue 17 (7th May 2015) - Stucchi, Mattia; Cairati, Silvia; Cetin-Atalay, Rengul; Christodoulou, Michael S.; Grazioso, Giovanni; Pescitelli, Gennaro; Silvani, Alessandra; Yildirim, Deniz Cansen; Lesma, Giordano
<x xml:space="preserve">Abstract</x> Three different chiral piperazine-based scaffolds have been synthesized using a Ugi/cyclization strategy.